The Effect of the Simulation Training on the Care of the Febrile Child: A Randomized Control Trial. - ARDAHAN AKGÜL, Esra; KARAKUL, Atiye; DOĞAN, Pınar; DOĞAN, Zehra; ÖZGÜVEN ÖZTORNACI, Beste (Journal of Nursology, 2023)
Objective: The purpose of this research is to examine the effect of simulation training on the students' knowledge of pediatric nursing care of a febrile child. Methods: This study was conducted with 48 students. Students were randomized into experimental (n = 24) and control (n = 24) groups. Data were collected through Sociodemographic Characteristics Form, Trait Anxiety Inventory, and Nursing Care Knowledge Form-Febrile Child. Statistical analysis of the study was performed in Statistical Package for the Social Sciences program. Wilcoxon and Mann-Whitney U tests were used for statistical analysis. Results: It was found that the students' knowledge scores in the experimental group were increased from 10.25 ± 1.51 to 11.33 ± 1.30 following the simulation training (P = .010). In the control group, it was found that the students' knowledge scores decreased from 10.33 ± 2.07 to 10.20 ± 1.66 after the theoretical training (P = .596). Conclusion: In this research, the simulation training was useful, and the student's knowledge scores increased. Simulation training is recommended to increase the knowledge of pediatric nurses about the care of children with fever.